Factors Influencing Visitors' Interest in Returning to Tourist Villages (Study at Ngilngof Tourism Village, Southeast Maluku) - Ramdhan Kurniawan; Shine Pintor Siolemba Patiro; Heru Suheryadi; Zulmi Ramdani (Khazanah Sosial, 2024)
This research aims to see the influence of tourist facilities, tourist attractions, and visitor satisfaction on interest in revisiting the Ngilngof Tourism Village in Southeast Maluku. A quantitative research design was used to answer these objectives. A total of 78 tourists were actively involved in this research, and they were visitors who made repeat visits, with the characteristic respondents being those who had visited at least two times or were making their 2nd visit to Ngilngof Tourism Village. A purposive sampling technique was used to select research respondents. Multiple regression data analysis with the help of SPSS was used to see the influence of the independent variable on the dependent. The research results show that both partially and simultaneously, the variables of tourist facilities, tourist attractions, and visitor satisfaction have a positive and significant effect (p<.05) on interest in repeat visits. Not only that, the contribution of these three variables reached 79.3%, which shows a huge influence on the dependent variable. The results of this research provide great benefits regarding the factors that must be maintained and improved by the managers of the Ngilngof Tourism Village so that tourist visits to their location will be even better.